Proceedings of the 12th International Workshop on Semantic Evaluation 2018
DOI: 10.18653/v1/s18-1185
|View full text |Cite
|
Sign up to set email alerts
|

NLITrans at SemEval-2018 Task 12: Transfer of Semantic Knowledge for Argument Comprehension

Abstract: The Argument Reasoning Comprehension Task requires significant language understanding and complex reasoning over world knowledge. We focus on transfer of a sentence encoder to bootstrap more complicated models given the small size of the dataset. Our best model uses a pre-trained BiLSTM to encode input sentences, learns task-specific features for the argument and warrants, then performs independent argument-warrant matching. This model achieves mean test set accuracy of 64.43%. Encoder transfer yields a signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Similar to our experiment with warrants, Poliak et al (2018) classified NLI data based on the hypothesis only. A similar experiment to our probing task was performed by Niven and Kao (2018), but only with reasons and warrants. They found that independent warrant classification with shared parameters provides some regularization against warrant-label cues (Niven and Kao, 2018).…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar to our experiment with warrants, Poliak et al (2018) classified NLI data based on the hypothesis only. A similar experiment to our probing task was performed by Niven and Kao (2018), but only with reasons and warrants. They found that independent warrant classification with shared parameters provides some regularization against warrant-label cues (Niven and Kao, 2018).…”
Section: Related Workmentioning
confidence: 99%
“…A similar experiment to our probing task was performed by Niven and Kao (2018), but only with reasons and warrants. They found that independent warrant classification with shared parameters provides some regularization against warrant-label cues (Niven and Kao, 2018). However, this does not solve the problem since the presence of a cue is enough to increase the logits for either warrant.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, when confronted with shifts in input distribution, such as those encountered during domain adaptation, with out-ofdistribution examples, or when faced with novel scenarios, LLMs exhibit challenges in adapting and providing reliable predictions. This suggests that LLMs may encounter difficulties in adjusting to new input distributions, potentially relying on biases ingrained during training [21] , [22], [23]. One type of bias observed is the strong co-occurrence correlation between certain class labels and specific lexical features.…”
Section: Related Workmentioning
confidence: 99%